DOI: 10.14264/uql.2020.845
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an industry safety leadership toolkit

Abstract: M. (in progress). Improving safety culture through leadership practices: A case study describing the implementation and evaluation of an evidence-based toolkit based on the LEAD model. Safety Science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 131 publications
(256 reference statements)
0
1
0
Order By: Relevance
“…Jha [27] stated that a team could give its best only when all members are mentally healthy. Casey [28] found that interventions, such as leadership, safety, and behavior monitoring, have a positive influence on an organization's SC. Physical and mental hazards are also associated with SC.…”
Section: Workplace Climatementioning
confidence: 99%
“…Jha [27] stated that a team could give its best only when all members are mentally healthy. Casey [28] found that interventions, such as leadership, safety, and behavior monitoring, have a positive influence on an organization's SC. Physical and mental hazards are also associated with SC.…”
Section: Workplace Climatementioning
confidence: 99%